Directions for effective existing buildings thermo - Savyovskyy, V. (Ways to Improve Construction Efficiency, 2015)
The article deals with the causes of heat loss through the exterior building envelope constructions of existing buildings and the necessity of their thermo. Are some of the features of work that need to be taken into account when developing solutions for thermal insulation constructions. Presented proposals to increase the effectiveness of insulation. Thermo-delineated areas of existing buildings.